2012
DOI: 10.3892/or.2012.2093
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by D-limonene is mediated by inactivation of Akt in LS174T human colon cancer cells

Abstract: D-limonene is recognized as a potential chemotherapeutic agent, however, the details of this mechanism remain unclear. In this study, we investigated the effects of d-limonene on colon cancer cell viability and its potential mechanism of action in vitro. After 48 h of treatment, d-limonene suppressed the viability of LS174T cells in a dose-dependent manner and caused a dose-dependent apoptotic cell death. D-limonene activated caspase-3 and -9 and PARP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 30 publications
5
81
0
3
Order By: Relevance
“…Our previous study has demonstrated that limonene showed antiproliferative activity on the same cell lines as tested above with IC 50 values ranging from 18.4 to 124.0 µg/mL, respectively [33]. Limonene also induces apoptosis in LS174T colon cancer cells and in a lymphoma cell line (35 µg/mL, IC 50 ) [34,35]. Moreover, it shows antitumor activity on lung adenocarcinoma A549 (0.098 µL/mL, IC 50 ) and hepatocarcinoma HepG2 cells (0.150 µL/mL, IC 50 ) [36].…”
Section: Discussionmentioning
confidence: 64%
“…Our previous study has demonstrated that limonene showed antiproliferative activity on the same cell lines as tested above with IC 50 values ranging from 18.4 to 124.0 µg/mL, respectively [33]. Limonene also induces apoptosis in LS174T colon cancer cells and in a lymphoma cell line (35 µg/mL, IC 50 ) [34,35]. Moreover, it shows antitumor activity on lung adenocarcinoma A549 (0.098 µL/mL, IC 50 ) and hepatocarcinoma HepG2 cells (0.150 µL/mL, IC 50 ) [36].…”
Section: Discussionmentioning
confidence: 64%
“…Our previous study has demonstrated that limonene showed antiproliferative activity on the same cell lines as tested above with IC50 values ranging from 18.4 to 124.0 μg/ml, respectively [31]. Limonene also induces apoptosis in LS174T colon cancer cells and in a lymphoma cell line (35 μg/ml, IC50) [32,33]. Moreover, it shows antitumor activity on lung adenocarcinoma A549 (0.098 μl/ml, IC50) and hepatocarcinoma HepG2 cells (0.150 μl/ml, IC50) [34].…”
Section: Discussionmentioning
confidence: 62%
“…Limonene effectively induced apoptosis in LS174T colon cancer cells by inhibiting phosphorylation of Akt and GSK-3β. Moreover, intrinsic pathway was noted to be activated in Limonene treated LS174T colon cancer cells (Jia et al, 2013). Limonene and docetaxel synergistically induced greater ROS production and considerably enhanced apoptosis in prostate cancer cells (Rabi and Bishayee, 2009).…”
Section: In Vitro Analysis Of Efficacy Of Limonenementioning
confidence: 99%